Foundations of data science based healthcare Internet of things - Mahalle, Parikshit N.; Sonawane, Sheetal S. (Singapore Springer, 2021)
This book offers a basic understanding of the Internet of Things (IoT), its design issues and challenges for healthcare applications. It also provides details of the challenges of healthcare big data, role of big data in healthcare and techniques, and tools for IoT in healthcare. This book offers a strong foundation to a beginner. All technical details that include healthcare data collection unit, technologies and tools used for the big data analytics implementation are explained in a clear and organized format.
Electronic reproduction
Keywords: Medical informatics; Internet of things; Big data; Electronic books